The The Agreement of Asset Separation in the Perspective of Maqasid al-Shariah: The Problem of Asset Conflict, the Hifdz al-Mal Approach, and Its Impact on Family Stability in Islamic Law in Indonesia - Edy Saputra; Mohammad Ridwan (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
This study analyzes marital property separation agreements through the lens of Maqasid al-Shariah, with a specific focus on the principle of Hifdz al-Mal (protection of wealth) as an essential tool for safeguarding individual financial rights within marriage and preventing asset conflicts that could threaten family stability. Employing a qualitative method with a library research approach and in-depth literature analysis, the study reveals that marital property separation agreements have a strong legal foundation in Islamic and Indonesian national law, reinforced by Constitutional Court Decision No. 69/PUU-XIII/2015. This decision affirms the legality of marital property separation agreements under Indonesian law as an effective mechanism for ensuring fair asset management and protecting the financial rights of couples. The study recommends enhancing relevant regulations to improve legal clarity, educating the public about the benefits of these agreements, and encouraging active roles for religious scholars to support more flexible interpretations of Islamic law that address modern socio-economic needs. Future research employing quantitative methods and cross-cultural studies in dual-legal system countries such as Malaysia and Tunisia is suggested to explore public perceptions, economic impacts on women, and potential adaptations to address similar legal challenges.